Unexpected Inflation, Capital Structure, and Real Risk‐adjusted Firm Performance. (2nd May 2017) - Alcock, Jamie; Steiner, Eva
Abstract : Managers can improve real risk‐adjusted firm performance by matching nominal assets with nominal liabilities, thereby reducing the sensitivity of real risk‐adjusted returns to unexpected inflation. The net asset value of US equity real estate investment trusts (REITs) serves as a good proxy for nominal assets and, accordingly, we use a sample of US REITs to test our hypothesis. We find that for the firms in our sample: (i) their real risk‐adjusted performance, and (ii) their inflation‐hedging qualities are inversely related to deviations from this 'matching‐nominals' argument. In addition to providing managers with a vehicle to maximize real risk‐adjusted performance, our findings also provide investors with the tools to infer inflation‐hedging qualities of equity investments.